Galaxy Zoo: Motivations of Citizen Scientists - Raddick, M; Bracey, G; Gay, P; Lintott, C; Cardamone, C; Murray, P; Schawinski, K; Szalay, A; Vandenberg, J (2013)
Citizen science, in which volunteers work with professional scientists to conduct research, is expanding due to large online datasets. To plan projects, it is important to understand volunteers' motivations for participating. This paper analyzes results from an online survey of nearly 11,000 volunteers in Galaxy Zoo, an astronomy citizen science project. Results show that volunteers' primary motivation is a desire to contribute to scientific research. We encourage other citizen science projects to study the motivations of their volunteers, to see whether and how these results may be generalized to inform the field of citizen science.